2017
DOI: 10.1021/acsomega.6b00399
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Doping on GO: Fast Response–Recovery Humidity Sensor

Abstract: Nowadays, humidity sensors have become essential in numerous applications. However, there are several problems while using them for humidity detection, such as low sensitivity, delayed response and recovery times, less stability, and narrow humidity detection ranges. Here, we demonstrate for the first time a highly sensitive chemiresistive sensor for low-level humidity detection in ambient atmosphere by introducing graphene oxide (GO) and doped GO (Li-doped GO and B-doped GO) as a thin film in a facile manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…For selective sensitivity the surface can be modified by catalyst particles or chemical agents to enhance charge transfer from detecting agent to GO layer. It was successfully demonstrated GO is good sensor for hydrogen [122], nitrogen dioxide [123], humidity [124,125].…”
Section: Sensors For Chemistry and Biologymentioning
confidence: 99%
“…For selective sensitivity the surface can be modified by catalyst particles or chemical agents to enhance charge transfer from detecting agent to GO layer. It was successfully demonstrated GO is good sensor for hydrogen [122], nitrogen dioxide [123], humidity [124,125].…”
Section: Sensors For Chemistry and Biologymentioning
confidence: 99%
“…They proposed that the enhanced sensitivity and the hysteresis of these sensors were based on the molecular interactions between the increased water and charged groups in GO at high pH, suggesting a trade-off relationship between sensitivity and hysteresis. In addition, various approaches have been employed to improve the sensing performance or application area of GO based humidity sensors, such as free-standing GO foam to increase the active site [120], ultralarge GO to improve the overall proton conductivity [121], silk fiber coated with GO to take advantage of silk fiber’s flexibility [122], computer-aided design [123], investigation of the influence of the structure and coating methods [124], heteroatom-doping on GO to improve the response [125], as well as microstructure related synergic sensing for high-performance humidity sensors [126].…”
Section: Humidity Sensors Based On Graphene Materialsmentioning
confidence: 99%
“…Lv et al demonstrated substantially improved sensitivity of boron‐doped graphene toward toxic vapors such as nitrogen dioxide and ammonia . In addition, Rathi and Pal synthesized Li‐doped GO and proved the excellent sensitivity toward humidity with fast response and recovery times …”
Section: Introductionmentioning
confidence: 99%
“…[14] In addition, Rathi and Pal synthesized Li-doped GO and proved the excellent sensitivity toward humidity with fast response and recovery times. [15] Recently, 1D fibrous graphene is gaining much interest with regard to versatile applications in wearable textiles. [16,17] As a new type of carbonaceous fiber, 1D graphene fiber is also highly advantageous for application in vapor detection since the fibers can provide high porosity for vapor adsorption on the surface.…”
Section: Introductionmentioning
confidence: 99%